Analyzing Open Innovation Dimensions Based on Information Technology Development in Knowledge-Based Firms: Integration of BSC, FANP and DEMATEL - Gholamreza Jamali (Journal of Information Technology Management)
The main purpose of this paper was to analyze open innovation dimensions based on IT development in knowledge-based firms using a combination of BSC, FANP and DEMATEL. Beginning with an overview of the related literature, criteria of open innovation were identified for knowledge-based firms, then, with the benefit of 15 experts, we considered 14 of those criteria. All selected criteria classified according to the four perspectives of the balanced scorecard (BSC) aspects framework. In the next step, criteria weights calculated using fuzzy analytic network process (FANP) technique. Finally, a super matrix developed to measure criteria interrelationships using DEMATEL technique. The results showed that customer criterion with a weight of 0.3, was the most important one influencing the open innovation in knowledge-based firms for the development of information technology. Learning criterion with 0.29, internal process criterion with 0.24 and financial criterion with a total weight of 0.17 were the next priorities.